Dynamic Immune Cell Recruitment After Murine Pulmonary Aspergillus fumigatus Infection under Different Immunosuppressive Regimens - Kalleda, Natarajaswamy; Amich, Jorge; Arslan, Berkan; Poreddy, Spoorthi; Mattenheimer, Katharina; Mokhtari, Zeinab; Einsele, Hermann; Brock, Matthias; Heinze, Katrin Gertrud; Beilhack, Andreas (Frontiers in Microbiology, 2016)
Humans are continuously exposed to airborne spores of the saprophytic fungus Aspergillus fumigatus. However, in healthy individuals pulmonary host defense mechanisms efficiently eliminate the fungus. In contrast, A. fumigatus causes devastating infections in immunocompromised patients. Host immune responses against A. fumigatus lung infections in immunocompromised conditions have remained largely elusive. Given the dynamic changes in immune cell subsets within tissues upon immunosuppressive therapy, we dissected the spatiotemporal pulmonary immune response after A. fumigatus infection to reveal basic immunological events that fail to effectively control invasive fungal disease. In different immunocompromised murine models, myeloid, notably neutrophils and macrophages, but not lymphoid cells were strongly recruited to the lungs upon infection. Other myeloid cells, particularly dendritic cells and monocytes, were only recruited to lungs of corticosteroid treated mice, which developed a strong pulmonary inflammation after infection. Lymphoid cells, particularly CD4+ or CD8+ T-cells and NK cells were highly reduced upon immunosuppression and not recruited after A. fumigatus infection. Moreover, adoptive CD11b+ myeloid cell transfer rescued cyclophosphamide immunosuppressed mice from lethal A. fumigatus infection but not cortisone and cyclophosphamide immunosuppressed mice. Our findings illustrate that CD11b+ myeloid cells are critical for anti-A. fumigatus defense under cyclophosphamide immunosuppressed conditions.